Catalytic Dry Reforming of Methane: Insights from Model Systems. Issue 8 (14th February 2020) - Wittich, Knut; Krämer, Michael; Bottke, Nils; Schunk, Stephan Andreas
Abstract: Catalytic dry reforming under industrially relevant conditions of high pressures and high temperatures poses severe challenges towards catalyst materials and process engineering. The demanding conditions under which the reaction is performed lead to a coupling of reactions occurring in the gas phase and reactions which are catalyzed by the material employed as catalyst. A profound analysis of the mechanisms occurring in gas phase and resulting products from gas phase reactions is key to understanding part of the challenges that any catalyst material, irrespective of its nature, will have to cope with. The deposition of coke on an active catalyst is as well one of the most limiting factors for catalyst lifetime and catalyst activity in dry reforming. Therefore, an understanding of the thermodynamics behind coke formation and an intricate description of the mechanisms driving the evolution of coke is a vital piece of the picture. Acid‐base properties of the catalyst material and the role and nature of the active metal do also need to be considered. A large part of the review deals with mechanisms which are relevant for coke gasification and insights into materials properties, which are relevant to allow for reaction pathways along these lines. The review article focusses on research results which have been achieved using model systems – typically the analysis of model systems is a more rewarding exercise compared to fully formulated industrial catalyst systems, as here more elucidating structure‐property relationships can be drawn. Additionally the article discusses dry methane reforming in the context of alternative syngas generation technologies and attempts to create an application perspective for the reader in the context of a sustainable approach towards carbon capture and storage. Abstract : Getting in formation : Coke formation is the main reason for deactivation in dry reforming of methane under industrially relevant conditions due to the necessary high temperatures (thermodynamic) and pressures (economical). Therefore, understanding coke formation is an important factor for the development of novel coke resilient catalysts systems with high activity and stability.